Yield and yield parameters of rice (Oryza sativa) as influenced by date of planting and age of seedlings - PATTAR, P S; MASTHANA REDDY, B G; KUCHANUR, P H (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at Agricultural Research Station, Gangavathi, during the rainy season (kharij) of 1998 and 1999 to study the influence of time of planting and age of seedlings on the performance of transplanted rice (Oryza sativa L.). Planting of rice during the first fortnight of August resulted in significantly higher grain yield (5.16 tonnes/ha) than later plantings. Aged seedlings of 45 days (4.75 tonnes/ha) performed better than the younger seedlings of 25 days (4.22 tonnes/ha) for grain yield. The interaction of planting date and age of seedlings was significant. The performance of different age-group seedlings was found at par when planted during the first fortnight of August. However, the performance of aged seedlings (35 or 45 days) under late planted conditions (second fortnight of August) may be compared with that of 25 days old seedlings planted during the first fortnight of August.